Pembentukan Umbi Lapis Mikro Dua Kultivar Bawang Merah (Allium cepa var. Aggregatum Group) pada Beberapa Konsentrasi Succunic Acid Daminozide Hydrazide - Dini Dinarti; Agus Purwito; Anas D Susila; Iis Rahmawati (Jurnal Ilmu Pertanian Indonesia, 2008)
The objective of this research was to study shallot bulb formation on few concentrations of growth retardant succinic acid daminozid hydrazide (SAOH). Completely Randomized Design with 2 factors were used in this experiment. The first factor was four concentrations of SAOH (0, 30, 60 and 90 ppm) and second was two cultivars of shallot (Bima Juna and Kuning Tablet). The cultivars did not give significant effect to total number of leaf, shoot, root, number and weight of bulb, diameter of bulb, and height of plantlets. While SADH concentrations gave very significant effect to number of leaf, but not significant to number of root, number and weight of bulb, diameter of bulb and height of plantlets. Combinations of the two factors only gave significant effect to number of leaf and shoot but not significant to number of root, number and weight of bulb and height of plantlets.   Keywords: bulb formation, SAOH, shallot